Tarenna harleyae (Rubiaceae), a new forest species from West Africa - Jongkind, Carel C.h. (Phytotaxa, 2021)
Tarenna nitidula, from West Africa is here divided into two separate species, T. nitidula s.s. and the new species T. harleyae, which is described and illustrated here. Tarenna harleyae differs from T. nitidula s.s. by its corolla tubes 6–8 mm long, glabrous inside (vs. 3–5 mm, puberulous), and calyx lobes 1–1.5 mm long (vs. < 1 mm long). Tarenna harleyae is found in the tropical lowland forest in Sierra Leone, Guinea, Liberia and Ivory Coast, while T. nitidula occurs from Guinea-Bissau to Ivory Coast.